Watershed Development in Red Soils - Mallikarjunappa Gowda, D.S.; Basavaraja, P.K.; Itnal, C.J. (Journal of Soil and Water Conservation, 2022)
In India most of the Agricultural land is dry land (70 per cent) with low production. If that area is maintained properly by conserving Soil and Water through Watershed approach, it will help in enhancing the crop yield per hectare in dry land areas and in addition will protect the huge loss of soil and water. Hill: this approach various soil conservation structures viz., Contour bunds. Rubble Checks, Vegetative barriers, Graded bunds and Gully pluggs etc., lucre tried in shallow red soil with micro watershed through National H’atershed Development Project for Rainfed Areas (NWDPRA).